Exploring the experience of communication in the care of children with palliative care needs: the perspectives of nurses, family carers and physicians in Jordan - Atout, Maha (2017)
Background: Despite having limited access to specialist palliative care, countries can successfully satisfy palliative care needs by ensuring all health professionals are properly trained and educated in their respective roles. Effective communication is a fundamental element in ensuring the quality of care provided to children with palliative care needs and has a considerable effect on the well-being of children as well as their relatives and care professionals. Nonetheless, a broad overview of the existing literature reveals that nurses often feel inadequately trained or prepared in terms of the communication skills needed to deal with the difficult situations. They often lack the confidence to communicate properly with parents or to deal with difficult questions or issues of conflict. Whilst this seems to echo studies previously conducted across a range of countries worldwide, research shows that countries with an Arab culture face slightly different issues in terms of disclosing serious prognoses to families. The current study is the first to examine communication between children, parents, and health professionals, in the care of children with non-malignant life-threatening and life-limiting illnesses in Jordan, and in particular the cultural and spiritual context that affects this communication.